A Commentary on Safety Precautions for Otologic Surgery during the COVID-19 Pandemic. (June 2020) - Saadi, Robert A.; Bann, Darrin V.; Patel, Vijay A.; Goldenberg, David; May, Jason; Isildak, Huseyin
There are insufficient data regarding the safety of otologic procedures in the setting of the coronavirus disease 2019 (COVID-19) pandemic. Given the proclivity for respiratory pathogens to involve the middle ear and the significant aerosolization associated with many otologic procedures, safety precautions should follow current recommendations for procedures involving the upper airway. Until preoperative diagnostic testing becomes standardized and readily available, elective cases should be deferred and emergent/urgent cases should be treated as high risk for COVID-19 exposure. Necessary otologic procedures on positive, suspected, or unknown COVID-19 status patients should be performed using enhanced personal protective equipment, including an N95 respirator and eye protection or powered air-purifying respirator (PAPR, preferred), disposable cap, disposable gown, and gloves. Powered instrumentation should be avoided unless absolutely necessary, and if performed, PAPR or sealed eye protection is recommended.